ANALISIS KAMPANYE #diindonesiaaja OLEH KEMENPAREKRAF DI MEDIA SOSIAL SEBAGAI RESOLUSI KEPARIWISATAAN PADA MASA PANDEMI - Pasaribu, Rotumiar (Linimasa : Jurnal Ilmu Komunikasi, 2021)
The issue of the pandemic is indeed a concern for every line considering the impact it has had. The tourism sector is no exception, which turned out to be the most influential sector due to the pandemic. The bad and declining sector of the pandemic has an impact on the country's economy. This is especially true for Indonesia, which shows that the highest foreign exchange for the country is the tourism sector. Therefore, the ministry of tourism and creative economy created the #diindonesiaaja campaign as a step to control this economic flow. This study aims to see this campaign activity through Instagram by measuring its suitability based on the 7Cs PR Communications. They are concept, credibility, context, content, clarity, continuity and consistency, channel and capability of the audience. This research uses descriptive qualitative method. This study uses information through social media Instagram with the hashtag #diindonesiaaja as the subject of research and measurement of the Public Relations work program, namely 7'Cs PR Communications as the object of research. The results of the study show that all the concepts of 7’Cs are well applied. Not only that, the response received by the target audience also shows that this campaign has been right on target. Tourists take trips that are only carried out in Indonesia and remain obedient to health protocols. The increasing number of audiences using #diindonesiaaja shows that this campaign is successful. So it can be concluded that the #diindonesiaaja campaign has become a program that is able to invite the target audience to travel so that the economic problems of the tourism sector begin to improve.